2020
DOI: 10.3390/cryst10070610
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Irradiation to Produce High Performance Thermoelectric Material Based on Al Doped ZnO Nanostructures

Abstract: Microwave irradiation is found to be effective to provide highly crystalline nanostructured materials. In this work, this technique has been used to produce highly improved thermoelectric (TE) material based on aluminum (Al) doped zinc oxide (ZnO) nanostructures (NSs). The effect of Al dopant at the concentration range 0.5–3 mol % on the structural and TE properties has been investigated in more details. The optimum concentration of Al for better TE performance is found to be 2 mol %, which could significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Zn 0.995 Al 0.005 O displays a large Seebeck coefficient with a negative sign (−590 µV/K), but the electrical resistivity is extremely high (Table 1). It is worth mentioning that Al doping is needed to improve the electrical properties of ZnO [37][38][39]. In this case, the electrical resistivity remains higher in comparison with other thermoelectric oxides (i.e., Ca 3 Co 4 O 9 ).…”
Section: Effect Of Nrgo and Exgr On The Thermoelectric Properties Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Zn 0.995 Al 0.005 O displays a large Seebeck coefficient with a negative sign (−590 µV/K), but the electrical resistivity is extremely high (Table 1). It is worth mentioning that Al doping is needed to improve the electrical properties of ZnO [37][38][39]. In this case, the electrical resistivity remains higher in comparison with other thermoelectric oxides (i.e., Ca 3 Co 4 O 9 ).…”
Section: Effect Of Nrgo and Exgr On The Thermoelectric Properties Of ...mentioning
confidence: 99%
“…As oxides, we chose p-type Ca 3 Co 4 O 9 and n-type Zn 0.995 Al 0.005 O. These oxides were selected due to their ability to modify the electrical and thermal properties through the regulation of the interface and boundary grains [37,38]. In addition, the thermal conductivity of oxides displays size-dependent effects, which allows for the suppression of thermal conductivity through effective phonon scattering [39].…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 also showed that a smaller grain size, which results in lower thermal conductivity, fits well with the Callaways model, as discussed in the previous section. For instance, Baghdadi et al 's 53 Al-doped ZnO nanoparticles synthesized by microwave irradiation method yielded nanometer-sized ZnO. The obtained ZnO grain size sample was 24.1 nm, where its thermal conductivity measured at 700 K was ∼2.2 W m −1 K −1 and 4 W m −1 K −1 at room temperature.…”
Section: Effective Parameters On Zno Grain Sizesmentioning
confidence: 99%
“…Another effective technique used to adjust nanostructure morphology/size of ZnO was using microwave irradiation and has been found by in providing highly efficient TE materials. 53 The reduction in grain size leads to a decrease in thermal conductivity due to phonon scattering at the grain boundaries. 103 A novel thermoelectric AI-doped ZnO ceramics with nanopowders size was proven enhanced TE performance through nano/microstructure engineered using synthesis technique.…”
Section: Effective Parameters On Zno Grain Sizesmentioning
confidence: 99%